8. EFFICACY OF SPINAL BLOCK WITH DIFFERENT DOSES OF ROPIVACAINE FOR CROSSEN TECHNIQUE IN PROLAPSE ORGAN OF PELVIS IN NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY (Vietnam Journal of Community Medicine, 2023)
Objectives: To evaluate the analgesic effect of the spinal block with different doses of Ropivacainefor Crossen surgery for prolapse organ pelvis at the National Hospital of Obstetrics and Gynecology.Subjects and research methods: The patients were diagnosed with prolapse organ pelvis and wereindicated for Crossen surgery. Results: Age, height, and weight were not different (p>0.05). TheRopivacaine 13 mg group had a higher level of sensory block at D4 than the Ropivacaine 11 mggroup and the Ropivacaine 12 mg group. The difference was statistically significant with p
Keywords: Genital prolapse, spiral block, National Hospital of Obstetrics and Gynecology.